Netralitas Aparatur Sipil Negara (ASN) dalam PILKADA untuk Mewujudkan Good Governance - Mochamad Riyanto; Agus Widodo; Rini Retnowinarni (Syntax Idea)
This conceptual article aims to elucidate the significance of the neutrality of Civil Servants (Aparatur Sipil Negara or ASN) in carrying out their duties and responsibilities, particularly in the context of regional head elections (Pilkada). Additionally, this research seeks to understand the challenges and implementation of ASN neutrality in simultaneous Pilkada and its implications on the application of the principles of good governance. This study adopts a conceptual approach that emphasizes field observations and literature-based analysis. The research findings demonstrate the crucial role of ASN, as a component of the state bureaucracy, in maintaining their neutrality when executing their responsibilities. The research documents various forms of ASN involvement in Pilkada, such as participating as campaign team members, using party attributes or ASN insignia, mobilizing other ASN, and utilizing state facilities. Laws and regulations have been established to prohibit ASN from engaging in campaign activities or providing support to regional head candidates. In conclusion, this article underscores that the neutrality of ASN is a pivotal principle in supporting good governance, particularly within the context of Pilkada. The challenges and implementation of ASN neutrality in simultaneous Pilkada have substantial implications for the democratic process and state administration. Therefore, concrete measures are necessary to ensure that ASN fulfills their duties professionally, neutrally, and in the service of the public without favoring any particular party. Reforming the bureaucracy and developing a meritocracy system are essential steps toward achieving this goal.